Food consumption of children younger than 6 years according to the degree of food processing - Ediana Volz Neitzke Karnopp; Juliana dos Santos Vaz; Antonio Augusto Schafer; Ludmila Correa Muniz; Rosângela de Leon Veleda de Souza; Iná dos Santos; Denise Petrucci Gigante; Maria Cecilia Formoso Assunção (Jornal de Pediatria (Versão em Português), 2017)
Objective: To evaluate food intake according to the degree of processing, stratified by family income and age, in a representative sample of children younger than 6 years in the city of Pelotas, RS, Brazil. Methods: Cross‐sectional population‐based study carried out with 770 children aged 0–72 months of age living in the urban area of Pelotas. The dietary intake of children was assessed by 24‐h recall administered to mothers or guardians. The energy intake was estimated and each food item was classified according to the food processing degree. Food consumption was stratified by age (younger than 24 months; 24 months; or older) and associations between quintiles of family income and relative contribution of each food to total energy were performed by linear regression. The Wald test was applied to test linear trend across groups. Results: The mean energy intake was 1725.7 kcal/day. The mean contribution of processed and ultraprocessed foods was 19.7% among children younger than 24 months and 37% in those aged 24 months or older, while the mean consumption of natural and minimally processed food was 61% and 44%, respectively. Among children aged 24 months or older, a greater consumption of canned foods, cheese and sweets was observed as family income quintiles increased, while breads were more consumed by those children belonging to the lower income quintiles. Conclusion: A high caloric contribution of ultraprocessed foods in detriment to a lower consumption of natural and minimally processed foods was observed in the diet of children younger than 6 years.